2013
DOI: 10.1007/s13197-013-1073-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asparagus racemosus (shatavari) extract on physicochemical and functional properties of milk and its interaction with milk proteins

Abstract: The effects of interaction of Asparagus racemosus (shatavari) with milk constituents and physico-chemical and functional characteristics of milk was studied. Addition of freeze dried aqueous shatavari extract at a concentration of 1 g /100 ml of milk showed a decrease in pH, rennet coagulation time and an increase in acidity, viscosity and heat stability at maximum. The extract also imparted brown colour to milk and showed an increase in a* (redness) and b* (yellowness) values but a decrease in L* (lightness) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…Control, 0.5 and 1.0% tulsi enriched milk showed statistically similar (p > .05) heat stability whereas 1.5% showed significant difference (p < .05) to control. A similar study was carried out in literature (Veena et al, 2015). They developed shatavari enriched milk and reported that a 1% addition of Shatavari extract increased heat coagulation time.…”
Section: Heat Stabilitysupporting
confidence: 56%
“…Control, 0.5 and 1.0% tulsi enriched milk showed statistically similar (p > .05) heat stability whereas 1.5% showed significant difference (p < .05) to control. A similar study was carried out in literature (Veena et al, 2015). They developed shatavari enriched milk and reported that a 1% addition of Shatavari extract increased heat coagulation time.…”
Section: Heat Stabilitysupporting
confidence: 56%
“…Freeze‐dried aqueous extract of asparagus‐fortified milk has antioxidative and immunomodulatory potential 103 . A 1 g addition of freeze‐dried aqueous extract of asparagus per 100 mL of milk decreases the rennet coagulation time, pH, and L * (lightness) value and increases the heat stability, viscosity, acidity, a * (redness), and b * (yellowness) values 104 . Asparagus's dried powder increases the proteolysis, antioxidant activity, and phenolic content and decreases the lipolysis indexes and pH of processed cheeses.…”
Section: Asparagus Powder or Its Extract For Value Addition Of Productmentioning
confidence: 99%
“…103 A 1 g addition of freeze-dried aqueous extract of asparagus per 100 mL of milk decreases the rennet coagulation time, pH, and L* (lightness) value and increases the heat stability, viscosity, acidity, a* (redness), and b* (yellowness) values. 104 Asparagus's dried powder increases the proteolysis, antioxidant activity, and phenolic content and decreases the lipolysis indexes and pH of processed cheeses. Asparagus incorporated into processed cheese is more elastic, with improved rigidity and reduced spreadability.…”
Section: Milk and Milk Productsmentioning
confidence: 99%
“…The smears were examined microscopically and scored according to the following guidelines. [18] 0-Diestrus phase-mainly leukocytes with few epithelial cells 1-Presence of mixture of leukocytes and epithelial cells 2-Proestrus phase-Presence of nucleated or nucleated plus corniified cells 3-Estrus phase-Presence of corniified cells only. Only animals showing score of 2 or 3 were considered to be positive for estrogenic activity.…”
Section: Effect On Vaginal Cornificationmentioning
confidence: 99%